1 Year Of Free Preparation For School In Preschool Educational Organizations, The Formation Of Research Skills Of Students (Eurasian Journal of Learning and Academic Teaching, 2023)
The problem of children's readiness for learning at school is one of the fundamental problems of pedagogy and psychology, has a long prehistory and a relatively short history. The need to prepare children for learning appeared in the process of developing education as a social form of interaction between people of different generations. The article considers the views on the problem of preparing children for schooling in different time periods